Arbovirus Detection of Adult Female Aedes aegypti for Dengue Surveillance: a Cohort Study in Bandung City, Indonesia - Faridah, Lia; Ekawardhani, Savira; Fauziah, Nisa; Djati, Imam Damar; Putra, Ramadhani Eka; Watanabe, Kozo (Global Medical & Health Communication (GMHC), 2023)
Dengue surveillance is an important activity to prevent dengue outbreaks. This activity becomes a significant challenge for the region with limited logistic capabilities. Developing a simple mathematical model to predict the possibility of dengue incidence provides a reliable early warning system. This study compared the correlation between vector (adult female Aedes aegypti) and arbovirus detection on a vector to dengue incidence, which generalized linear mixed models tested. The incidence of adult female Aedes aegypti and dengue fever cases were interpolated through third-power inverse distance weighting (IDW). A spatial correlation between female Aedes aegypti incidence and dengue incidence was obtained from polynomial regression. Collection sites were 16 villages in Bandung city, one of the significant dengue endemic areas in January–December 2017. A total of 8,402 mosquitoes of Aedes aegypti, Aedes albopictus, and Culex sp., with 17% belonging to Aedes aegypti as the subject of the dengue virus (DENV) infection test. Data analysis only showed a weak correlation between the numbers of adult female Aedes aegypti and dengue incidence. On the other hand, there is no correlation between positive dengue infection of vector and dengue incidence. This study highlights the importance of constant arbovirus surveillance and integrated surveillance methods on all possible dengue vectors to develop an early warning system for dengue incidence.